Enhancing the sensitivity of gamma-aminobutyric acid and glutamate biosensors by electrochemically roughening platinum microelectrodes - Adediji, Musefiu Yemi; Billa, Sanjeev; Siddiqui, Shabnam; Arumugam, Prabhu U. (Frontiers in Neuroscience, 2025)
Gamma-aminobutyric acid (GABA) and glutamate (GLU) are two key neurotransmitters (NTs) in processing, plasticity, memory, and network functions. High-sensitivity GABA and GLU biosensors are crucial for investigating the dysregulation of the GABA-GLU balance and improving animal models and human therapies for multiple neurological disorders. We have developed a novel biosensor that utilizes electrochemically roughened (ECR) platinum (Pt) microelectrodes to achieve the highest sensitivity in detecting hydrogen peroxide (H2O2), which serves as the detection signal for the biosensors. We evaluated three microelectrode surface activation techniques—alcohol cleaning, electrochemical cleaning, and ECR—and the main effects of the ECR pulses at varying frequencies (150–6,000 Hz) on biosensor sensitivity. ECR-treated microelectrodes reveal a non-linear relationship between the pulse frequency and the H2O2 adsorption, providing the highest sensitivity. Each frequency altered the microelectrode’s roughness differently, resulting in unique surface morphologies and pore geometries, as well as the formation of surface impurities within the pores. The primary factors influencing Pt’s electrocatalytic activity are the pore geometry and the facile Pt kinetics, and not the electroactive area or the impurities in the pores. Particularly, pore geometries at low (250 Hz) and high frequencies (2,500 Hz) contribute to the highest H2O2 adsorption and sensitivity (6,810 ± 124 nA μM−1 cm−2), the highest value reported in the literature. The EIS model reveals that ECR-treated microelectrodes exhibit heterogeneous pores and partially smooth, flat regions between the pores, with the catalytic activity primarily occurring in the pore walls rather than the flat regions. The EIS data indicate superior electrical conductivity in the pore walls, which enhances the GABA and GLU peak sensitivities to 45 ± 4.4 nA μM−1 cm−2 and 1,510 ± 47.0 nA μM−1 cm−2, respectively. The corresponding limits of detection are 1.60 ± 0.13 nM and 12.70 ± 1.73 nM (n = 3). These findings underscore the significance of ECR in enhancing the performance of Pt MEA-based enzymatic biosensors, thereby paving the way for advanced, ultrasensitive biosensors for neurochemical monitoring in challenging in vivo applications.